On 2-absorbing and strongly 2-absorbing ideals of commutative semigroups - (:unkn) unknown (Universitatii Al.I.Cuza din Iasi, 2016)
In this paper, S denotes a commutative multiplicative semigroup with 1 and 0. A nonempty subset I of S is called an ideal of S if I satisfies the condition SI ⊆ I. We introduce and investigate the concepts of 2-absorbing ideals and strongly 2-absorbing ideals of S. Also, we study the relationships between 2-absorbing ideals and strongly 2-absorbing ideals of S. © 2016, Universitatii Al.I.Cuza din Iasi. All rights reserved.
Keywords: 2-absorbing ideals; Commutative semigroups; Strongly 2-absorbing ideals